The key factors for a learning space: time, space and activity - Silva, P.N. Moreira da (2018)
Technology is a valuable tool in education both to increase access to knowledge and to promote learning. On the one hand, the ability of ICTs to centralize and organize large amounts of knowledge and, on the other hand, the students' familiarization with information networks and the internet, aims to interconnect students in networks and learning communities. Much has been studied about how spaces should be designed to enhance this type of learning. New learning environments are being built from scratch, others are simply altered or reformulated to respond to changes in pedagogical styles to incorporate ICT. In an age where the real and the virtual coexist, the learning spaces must be designed and adapted to concretize these realities. In this study I will present the main premises that should support the construction or transformation of several specific Learning Spaces to make possible the existence of two worlds, the real and the virtual. In this context, we propose three new variables that parallel technology will play a key role in the future learning space, (i) Time, (ii) Space, (iii) Activity. If we consider that the occupation of a Learning Space implies available time and if learning is not fixed by time or place, we find that the learning space needs a conjugation between space and time. Higher Education Institutions have to be more efficient in the use of time, where different times may have different learning experiences with different conjugations. Effective learning involves Time, Space and Activity that is developed within it, which distinguishes it from other spaces. A new experiment is suggested using those new variables to elucidate the construction of High Quality Learning Environments.